(untitled) (Bangladesh Rice Journal, 2020)
Northwestern part of Bangladesh plays an important role to supply rice for national food security. However, wet season (WS) rice cultivation in the area is highly vulnerable to moisture stress and severe pest infestation. Therefore, it is very much important to evaluate the adoption situation of wet season rice cultivars and their drivers and drawbacks of adoption in order to delineate the possible ways of rapid dissemination of modern rice varieties to cope with the existing vulnerability and minimize yield gap. Two important wet season rice-growing districts, namely Rangpur and Dinajpur were selected purposively for the study. Focus group discussion (FGD) and key informant interview (KII) were conducted using semi-structured questionnaire to gather qualitative and quantitative data for the study. In addition, structured questionnaire was used in the FGD for generating data on input use patterns, outputs and seasonal variability of yield and price of different rice cultivars for estimating costs and returns. The findings of the study reveal that farmers mainly adopted exotic WS rice cultivars to reduce unexpected yield loss due to abiotic and biotic stresses. Diffusion status of exotic cultivars was ranged between 76-85% of total WS rice area in the study locations. The drivers of widespread diffusion of exotic cultivars are stability in yield performance, compatibility to fit into local cropping systems, potentiality to recover from biotic and abiotic stresses and ensured market demand. However, farmers are dreaming for higher yield potential and more stress tolerant cultivars for fitting into two and three crops-based systems in the areas. Rice breeders may use the findings of this study to develop and disseminate suitable rice cultivars for the northwestern part of the country. Bangladesh Rice j. 2019, 23(1): 81-106